Verbesserung der Leistung der unteren Extremitäten bei Widerstandsbelastungen Widerstandsfähigkeit mit Durchblutungsstörung nach akuter Koffeinzufuhr - Souza, D. B.; Duncan, M.; Polito, M. D. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To examine the effects of acute caffeine (CAF) intake on physical performance in 3 sets of unilateral knee extensions with blood-flow restriction. Methods: In a double-blind crossover design, 22 trained men ingested 6 mg/kg of CAF or a placebo (PLA), 1 h prior to performing unilateral knee-extension exercise with blood-flow restriction until exhaustion (30% of 1 maximal repetition). Results: There was a significant difference in the number of repetitions between the CAF and PLA conditions in the first set (28.3 [5.3] vs 23.7 [3.2]; P = .005), second set (11.6 [3.1] vs 8.9 [2.9]; P = .03), and total repetitions performed across the 3 sets (44.5 [9.4] vs 35.0 [6.6]; P = .001). Blood lactate was also significantly different (P = .03) after exercise between the CAF (7.8 [1.1] mmol/L) and PLA (6.0 [0.9] mmol/L). In regard to pain perception, there was a difference between the CAF and PLA in the second (6.9 [1.5] vs 8.4 [1.4]; P = .04) and third sets (8.7 [0.4] vs 9.5 [0.6]; P = .01). No differences were found for perceived effort. Conclusion: Acute caffeine intake increases performance and blood lactate concentration and reduces perception of pain in unilateral knee-extension exercise with blood-flow restriction.